Georgia : Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
In light of its strategy for an accelerated transition to a market economy, Georgia has made tremendous efforts to provide a legal base for the required changes, and has adopted a multitude of laws at a rapid pace, starting in 1993. With the notable exception of enforcement provisions, the scope of existing Georgian legal instruments, would be adequate to control the procurement process in Georgia, if they were widely followed. The main issue is not the lack of legislation, but rather the effective application of the legislation that is already in place. Nevertheless, the Government's determination, and technical assistance provided under a Bank Institutional Development Fund, public procurement is now guided by a single overarching law. But, despite an acceleration in establishing a sound legal framework, the procurement reform agenda has not yet been completed, and procurement reform is going very slowly. Within this context, this Country Procurement Assessment Report (CPAR) recommends that: the list of procurement, identified as relating to national security, be cleared by the State Procurement Agency (SPA) to ensure that Power Bodies procure general items in accordance with the Law on State Procurement (LSP); foreign bidders be allowed greater access, and open and restricted bidding be more broadly applied; the state procurement agency be given a truly independent status, beyond the reach of influence of the Ministry of Economy, Industry and Trade, for it needs to be free to implement its mandate as a regulating and monitoring body that ensures compliance with the LSP. Given recent political developments to establish a Cabinet of Ministers, the CPAR further recommends that the current governance structure be reconsidered, and that the SPA be put under the Cabinet's control, provided with proper funding from the State budget, essential for it to implement its functions successfully; and finally, the CPAR recommends a full range of legal, regulatory, budgetary, training, dissemination, audit reform, and value-shifting measures to establish incentives for complying with the procurement law in particular, and to foster the growth of a culture of compliance in general.